Study on non - audible acoustic communication uplink for bidirectional visible light communication - Han, Doohee; Lee, Kyujin (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, we present a problem of conventional unidirectional visible light communication and limited bidirectional visible light communication, and propose a suitable uplink feedback communication structure.Methods/Statistical analysis: In the visible light communication environment using only the conventional LED, bidirectional communication for feedback of user data information between the transmitter and receiver is limited. When all the receiving devices transmit the feedback information through the LED light source, it is inconvenient for the users due to the unnecessary light source generation in the indoor lighting environment due to the characteristics of the visible light communication system performing both the communication and the illumination. In addition, interference due to a plurality of light sources occurs, and the performance of the system is deteriorated.To solve this problem, we propose the uplink system configuration using the non - audible band acoustic wave communication in the visible light communication system.Findings: The uplink transmission is a necessary function for transmitting the feedback information of the terminal, and a transmission scheme capable of ensuring sufficient transmission distance, interference elimination of LED illumination, and power efficiency should be used. In this paper, we have solved the problem of optical interference between downlink transmission and uplink transmission by securing transmission distance using non - audible band acoustic communication.In addition, the problem of the conventional unidirectional visible light communication can be solved by actively transmitting a signal to a channel state change due to communication distance or communication environment change through state information and position information feedback of devices using non-audible sound wave communication.Improvements/Applications: The non-audible sound wave communication uplink system can be applied as fusion technology to various environments such as an IoT network environment requiring a bidirectional network or an indoor small-scale network configuration and a home network configuration.Â